Generations, modernity and collective subjectivity - Domingues, José Maurício (Tempo Social, 2002)
Generations as a sociological question, conceptually and empirically, have received some attention recently. However, they remain undertheorized, in general in terms of their particular configurations in modernity. This article reviews the sociological and anthropological literature about the topic and proposes to reconceptualize it, drawing upon the concept of "collective subjectivity". It then resumes its analyses in the bounds of modern society.